Menstrual status and bone mineral density among female athletes - Sriareporn Punpilai (2018)
The present study investigated the relationship between menstrual status and bone mineral density (BMD). Sixty-three elite female athletes competing at the regional level participated. Self-reported menstrual status, stress during the past 6 months, dietary intake of calcium, blood samples for hormonal study, mid-thigh skinfold thickness, triceps, iliac crest, spine and femoral neck BMD were determined. It was found that more than half of the athletes were eumenorrheic while almost half were menstrually dysfunctional. The bone mineral density at the lumbar spine and the femoral neck were within normal ranges. Menstrual dysfunction in female athletes was related to a low BMD at the lumbar spine but not at the femoral neck. Delayed menarche and menstrual dysfunction during the first 2 years after menarche were related to current menstrual dysfunction, but low percent body fat was not related to menstrual dysfunction. This study suggests that exercise in elite female athletes might be an underlying cause of menstrual dysfunction and that there is a relationship between lumbar spine BMD and menstrual dysfunction. The assessment of menstrual history and percent body fat could be used as a screening tool for menstrual dysfunction. © 2005 Blackwell Publishing Asia Pty Ltd.